Evolução dos padrões epidemiológicos da prevalência de retinopatia diabética na diabetes mellitus tipo 1 entre 1990 e 2018: Estudo retrospetivo de uma população portuguesa - Miguel Carvalhais Valente Campos Lopes (2020)
Purpose: To estimate the prevalence of diabetic retinopathy /(DR) in a Portuguese population with type 1 diabetes (T1DM). Methods: Retrospective review of all patients with T1DM, whose reference center was Centro Hospitalar de São João, a tertiary center in Portugal, who were diagnosed between 1990 and 2018. DR was classified based on fundus examination in medical records as (0) no evidence of retinopathy, (1) mild non-proliferative retinopathy (NPDR); (2) moderate to severe non-proliferative retinopathy (NPDR) and (3) proliferative retinopathy (PDR). Patients were classified according to the eye with a worse retinopathy stage. Follow-up was considered as time between the diagnosis of diabetes and the last funduscopic evaluation. Results: 233 patients met the inclusion and exclusion criteria. The prevalence of any DR at less than 5, 10, 15, 20 and more than 20-years of DM was 1.8%, 10.4%, 34.8%, 54.1% and 71.2% respectively. The overall prevalence of DR was 43.3% (n = 101). At the last observation, 43 patients (18.5%) had mild NPDR, 34 patients (14.6%) had moderate to severe NPDR and 24 patients (10.3%) had PDR. The longer the disease duration, the higher the number of patients with DR. Conclusion: The prevalence of DR in our cohort was 34.8% after 15 years of systemic disease and 54.1% after 20 years, which is lower than what has been reported in the literature. Further multicentric prospective studies, are needed to clarify changes in the epidemiology of DR in type 1 diabetics.